Changes in sera proteome in relation to day of pregnancy in early pregnant buffaloes - BALHARA, A K; GUPTA, MEENAKSHI; MOHANTY, A K; PHULIA, S K; SHARMA, R K; SINGH, SURENDER; SINGH, INDERJEET (The Indian Journal of Animal Sciences, 2014)
The present study was planned for studying the sequential changes in early pregnant buffalo for the development of diagnostics for early pregnancy. In the present study, sera samples obtained at weekly intervals from early pregnant (day 0 to day 42 post-AI) buffaloes, and on days 0, 7 and 14 from non-pregnant cyclic buffaloes, were subjected to depletion of high abundant proteins followed by 2-dimensional gel electrophoresis and densitometric analysis. At least 65 2-D gel spots exhibited up-regulation, down-regulation or specific appearance at a specific stage during early buffalo pregnancy, except for the spots correlating with the high abundant proteins’ location. Comparison with ExPASy and NCBI databases matched 48 of these spots with known proteins, but with varying degrees of confidence in terms of Mascot score and the species. Although high abundant proteins were depleted before 2-D electrophoresis, yet in some of the picked spots isoforms of common abundant proteins, viz. serum albumin, igg, serrotransferrin, complement and mhc molecules, were found. synaptojanin-1, apolipoprotein a-1, apolipoprotein b, keratin 10 and von Willebrand factors were some of the proteins identified in these spots, which have a documented role in embryogenesis and early pregnancy.